Modification of the thermogenic effect of acutely inhaled salbutamol by chronic inhalation in normal subjects. Issue 9 (September 1993) - Wilson, S R; Amoroso, P; Moxham, J; Ponte, J
Abstract : BACKGROUND–Acute inhalation of clinical doses of salbutamol in normal volunteers increases resting metabolic rate by up to 20% above control values. This study was designed to see if chronic treatment with salbutamol causes a sustained increase in metabolic rate and whether it modifies the acute thermogenic response to the drug. METHODS–The effects of chronic inhaled salbutamol on resting oxygen consumption (VO2) and carbon dioxide output (VCO2) were studied in seven normal subjects (age 20-47 years, weight 52-105 kg, five men). An open canopy method of indirect calorimetry was used to measure VO2, VCO2, and respiratory quotient (RQ). Subjects inhaled two puffs of salbutamol or placebo four times a day in a double blind manner. Measurements of resting VO2 and VCO2 after 10 days of salbutamol were compared with the values after 10 days of placebo and with those taken at the start of the study. At the end of each treatment period subjects inhaled eight puffs (800 micrograms) of salbutamol and the acute effects on VO2, VCO2 and RQ were monitored for one hour. RESULTS–Resting VO2, VCO2, and RQ were not significantly different at the end of the salbutamol and placebo periods but the acute response to eight puffs of salbutamol was abolished by regular inhalation. The mean VO2 integrated over one hour after 800 micrograms salbutamol given acutely was different (241.3 and 210.7 ml/kg/h in the placebo and salbutamol groups respectively). Differences were not significant between placebo and salbutamol groups for changes in VCO2, heart rate, blood pressure, and RQ after acute inhalation. CONCLUSION–Regular treatment with inhaled salbutamol (800 micrograms/day) does not cause a sustained increase in resting metabolic rate but prevents the increase in VO2 that occurs after acute inhalations in normal subjects.